Cash Expenditure Accounting System on Pt. Pelni Cabang Medan - Eva Rianty Angelina Sitanggang*; Leonardo Lumbanraja; Syamsuddin Syamsuddin (Universitas Syiah Kuala, 2023)
The application of a cash disbursement accounting system in a company is very important because by implementing a cash disbursement accounting system, the company can monitor and control the course of the company's operating activities so that they can run as they should. Likewise with PT. PELNI implements a cash disbursement accounting system which consists of elements that are closely related to each other, namely documents used, records used, functions that are closely related, reports produced, internal controls, and cash disbursement flows. However, there are several elements whose implementation is not in accordance with the existing theory, so it is necessary to conduct research and study the existing system at PT. PELNI. From the results of this study, a discussion was obtained that the use of documents for cash disbursements must be distinguished for cash disbursements whose nominal amounts are large and whose nominal amounts are relatively small. The merging of functions in the cash disbursement process is not justified because it will trigger acts of abuse of the authority given resulting in fraud and misappropriation of company cash. Formation of petty cash in the company for relatively small expenses is really needed because it will be easier to handle and supervise.